Missed, rationed or unfinished nursing care: A scoping review of patient outcomes - Kalánková, Dominika; Kirwan, Marcia; Bartoníčková, Daniela; Cubelo, Floro; Žiaková, Katarína; Kurucová, Radka (Journal of nursing management, 2020)
AIMS: To collate evidence about patient outcomes resulting from the phenomenon of incomplete nursing care described in the literature variously as missed, rationed, or unfinished nursing care. BACKGROUND: Nursing care which is not completed is known to have a negative impact on patients. However, to date, there has been no thorough exploration of the extent and potential seriousness of patient outcomes. METHODS: The search was performed in four scientific databases; 44 studies were included in the final content analysis. RESULTS: Missed, rationed and unfinished care negatively influence the patient outcomes in the context of patient safety and quality of nursing care. Despite the differences among concepts, the negative association with patient outcomes was significant and common for all concepts. CONCLUSION: Awareness of potential harm of the phenomena to patient outcomes may help the management to develop preventive strategies to reduce or eliminate its actual occurrence. IMPLICATIONS FOR NURSING MANAGEMENT: Hospital management should consider the phenomenon as an indicator of the quality of nursing care as well as establish the routine monitoring of the phenomena in the assessment of patient safety in healthcare facilities.
Keywords: missed care; bezpečnost pacientů; Humans; patient outcome; rationed care; ošetřovatelská péče; Patient Safety; unfinished care; lidé; scoping review; Nursing Care